Management Boards and Indonesia's Company Innovation Performance - Desi Ilona; Zaitul Zaitul; Eugene Okyere Kwakye (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2021)
This study aims to investigate the influence of the management board's characteristics on company innovation performance. Management board characteristics are female in the management board, education background, and Chinese ethnicity in the management board. Resources dependency theory is applied to understand the research phenomena. Using 109 companies listed in the Indonesian stock market, multivariate regression analysis was employed. This study also employed five control variables: family ownership, foreign ownership, company profitability, company leverage, and company size. The result shows that female in management board is negatively related to innovation performance. Besides, family ownership, company profitability, company leverage, and company size positively affect innovative performance.